Endo-perio dilemma: A brief review - Preetinder Singh (Wolters Kluwer Medknow Publications, 2011)
The actual relationship between periodontal and pulpal disease was first described by Simring and Goldberg in 1964. Since then, the term "perio-endo" lesion has been used to describe lesions due to inflammatory products found in varying degrees in both the periodontium and the pulpal tissues. The pulp and periodontium have embryonic, anatomic and functional inter-relationships. The simultaneous existence of pulpal problems and inflammatory periodontal disease can complicate diagnosis and treatment planning. A perio-endo lesion can have a varied pathogenesis which ranges from quite simple to relatively complex one. Knowledge of these disease processes is essential in coming to the correct diagnosis. This is achievable by careful history taking, examination and the use of special tests. The prognosis and treatment of each endodontic-periodontal disease type varies. Primary periodontal disease with secondary endodontic involvement and true combined endodontic-periodontal diseases require both endodontic and periodontal therapies. The prognosis of these cases depends on the severity of periodontal disease and the response to periodontal treatment. This enables the operator to construct a suitable treatment plan where unnecessary, prolonged or even detrimental treatment is avoided.